2022
DOI: 10.3389/fnhum.2022.826376
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Classifiers to Evaluate Data From Gait Analysis With Depth Cameras in Patients With Parkinson’s Disease

Abstract: IntroductionThe assessments of the motor symptoms in Parkinson’s disease (PD) are usually limited to clinical rating scales (MDS UPDRS III), and it depends on the clinician’s experience. This study aims to propose a machine learning technique algorithm using the variables from upper and lower limbs, to classify people with PD from healthy people, using data from a portable low-cost device (RGB-D camera). And can be used to support the diagnosis and follow-up of patients in developing countries and remote areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…Several studies included in the review (n=10) reported machine learning classifier outcomes for identifying people living with dementia, MCI or PD from control [19,25,[29][30][31]33,[35][36][37]46] whereas several others (n=8) reported models that computed clinical assessment scores [17,18,24,34,[38][39][40][41]. Although these are useful outcomes, it is important to note that models that help detect gait impairment and predict falls (n=5) [14][15][16]27,32] could potentially be more useful in practical applications for assessing functional performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies included in the review (n=10) reported machine learning classifier outcomes for identifying people living with dementia, MCI or PD from control [19,25,[29][30][31]33,[35][36][37]46] whereas several others (n=8) reported models that computed clinical assessment scores [17,18,24,34,[38][39][40][41]. Although these are useful outcomes, it is important to note that models that help detect gait impairment and predict falls (n=5) [14][15][16]27,32] could potentially be more useful in practical applications for assessing functional performance.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 18 studies that included PD patients, 10 reported the use of the Kinect sensor for analysing gait, including its feasibility to extract relevant features [26,27] ability to detect PD [28][29][30][31] , and ability to measure clinical disease severity [32][33][34] . Alternative MMC models using image processing for pose estimation from videos recorded with RGB cameras have also been used with PD patients demonstrating the feasibility of these models in quantifying gait impairment and disease severity [18,[35][36][37][38][39][40][41].…”
Section: Patient Groupsmentioning
confidence: 99%
See 1 more Smart Citation